Atmospheric deposition levels of chosen elements in the Czech Republic determined in the framework of the International Bryomonitoring Program 1995 - Sucharová, J; Suchara, I (The Science of the total environment, 1998)
In order to determine the atmospheric loads of 13 elements (Al, As, Cd, Co, Cr, Cu, Fe, Mo, Ni, Pb, S, V, Zn), samples of Pleurozium schreberi (81.1%), Hypnum cupressiforme (11.2%) and Pseudoscleropodium purum (7.7%) bryophytes (mosses) were taken and analysed from an approx. 20 x 20-km grid extending over the entire territory (78,864 km2) of the Czech Republic (abbreviated 'the CZ' in this study). The level of the elements found in the bryophytes reflects the relative atmospheric deposition loads of the elements at the investigated sites. Five hot spots indicating relatively high deposition levels were identified in the CZ. The marginal hot spots are the following: the CZ part of the so-called Black Triangle I territory in northwestern CZ; the CZ part of the Black Triangle II territory in northeastern CZ; and the CZ part of the Sudeten mountains (Jizerské Mts and Giant Mts) and their foothills in northern CZ. Inland hot spots were found in the southwestern industrial part of central Bohemia and in the southern Moravian industrial district. The average element contents in CZ bryophytes were comparable with the respective average values obtained in Germany and Poland. However, the CZ average bryophyte values were higher and lower in comparison to the average Austrian and Slovak values, respectively. The CZ average relative atmospheric deposition loads of the elements were found to be 2-3 times higher than the respective loads in the cleanest parts of Europe (e.g. clean parts of Nordic countries). A comparison of the analytical results obtained repeatedly at 20 identical localities in the CZ showed a significant decrease in the relative deposition loads of all of the investigated elements in 1995 as compared to 1991. This decrease has been caused by the dramatic restriction of the industrial production, mainly that of the metallurgical and chemical industries, in the CZ. Desulphurisation programs and the effective trapping of flying dust particles in CZ power plants has also had a positive influence on the deposition climate in the CZ. The average values for the absolute atmospheric deposition of the investigated elements in the CZ in 1994-1995 as found from bryomonitoring are presented in this paper.
Keywords: Species Specificity; Environmental Monitoring; mechy; látky znečišťující vzduch; Metals, Heavy; monitorování životního prostředí; těžké kovy; Česká republika; druhová specificita; Bryopsida; kovy; Air Pollutants; Metals; Czech Republic